COMPETENCY MAPPING OF GRADUATE LEARNING OUTCOMES IN STRENGTHENING THE INDEPENDENT CAMPUS CURRICULUM - Ida Royandiyah; Gunawan Wiradharma; Rachmawati Windyaningrum; Isma Dwi Fiani; Nila Kusuma Windrati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
This study aimed to determine the mapping of graduate learning achievement competencies in strengthening the independent campus curriculum. This research uses mixed-method approach with descriptive research to overview the mapping of the learning achievement competencies of graduates needed by students, graduates, and users of the Bachelor Communication Studies Program at the Universitas Terbuka. The methods of data collection in this study using documentation review techniques, interviews and surveys. Based on the results of the data and research analysis, it can be concluded: 1) The suitability of the field of work according to the alumni has the suitability of the field of communication; and 2) Based on the results of the research, the competency aspect of the attitude aspect is 100% obtained by the alumni, while the industry needs for the attitude aspect is 98.7%. The general skill competency obtained by alumni is 97.8%, while 100% of industry needs are indispensable in work. The knowledge aspect competence obtained by the alumni is 97.2%, while the industrial needs in the knowledge aspect are needed at 94.2%. The competency aspect of special skills obtained by alumni is 89.8%, while industry needs, according to alumni, are 100% for all elements contained in particular skills.